A comparison of reactive strength in elite and sub-elite male and female Australian footballers - Southey, B. M.; James, L. P.; Connick, M. J.; Austin, D. J.; Wellington, B. M.; Green, M. J.; Scott, T. J.; Spits, D. R.; Beckman, E. M. (Sports Biomechanics, 2025)
Reactive Strength Index (RSI) correlates to locomotor performance, hence an important strength quality to develop in Australian footballers (AF). However, two common tests, the drop jump (DJ) and 10/5 repeated jump (RJ), have been suggested to reflect different qualities. Therefore, the aim was to compare RSI between the DJ and RJ. Additionally, AF cohort comparisons were made to observe impacts of competition level and sex on RSI. RJ, DJ and Isometric Mid-Thigh Pull (IMTP) tests amongst elite male (AFL, n = 21), female (AFLW, n = 19), and sub-elite male (U18B, n = 19) and female (U18G, n = 19) cohorts were explored over three testing sessions. Coefficient of determination and spearman`s rank correlation compared relationships between RJ, DJ and IMTP. Analysis of variance was used to compare strength qualities across AF cohorts. p < 0.05. Results found DJ and RJ had low shared variance (r2) 0.32. Furthermore, cohort comparisons found significant competition level and sex differences between reactive strength qualities. This study found that the RJ and DJ represent different reactive strength qualities, with differences in age and sex found in both. Therefore, both DJ and RJ should be considered when holistically examining reactive strength in AF, and the reactive quality ratio can highlight these relative differences.